NMDA Receptor Glycine Binding Site Modulators for Prevention and Treatment of Ketamine Use Disorder - Yu-Chin Hsiao; Mei-Yi Lee; Ming-Huan Chan; Hwei-Hsien Chen (MDPI AG, 2023)
Ketamine offers a fast-acting approach to relieving treatment-resistant depression, but its abuse potential is an issue of concern. As ketamine is a noncompetitive N-methyl-D-aspartate receptor (NMDAR) ion channel blocker, modulation of NMDAR might be an effective strategy to counteract the abuse liability of ketamine and even to treat ketamine use disorder. This study evaluated whether NMDAR modulators that act on glycine binding sites can decrease motivation to obtain ketamine and reduce reinstatement to ketamine-seeking behavior. Two NMDAR modulators, D-serine and sarcosine were examined. Male Sprague-Dawley rats underwent training to acquire the ability to self-administer ketamine. The motivation to self-administer ketamine or sucrose pellets was examined under a progressive ratio (PR) schedule. The reinstatement of ketamine-seeking and sucrose pellet-seeking behaviors were assessed after extinction. The results showed that both D-serine and sarcosine significantly decreased the breakpoints for ketamine and prevented reinstatement of ketamine seeking. However, these modulators did not alter motivated behavior for sucrose pellets, the ability of the cue and sucrose pellets to reinstate sucrose-seeking behavior or spontaneous locomotor activity. These findings indicate that two NMDAR modulators can specifically reduce the measures of motivation and relapse for ketamine in rats, suggesting that targeting the glycine binding site of the NMDAR is a promising approach for preventing and treating ketamine use disorder.